EVALUATING THE EFFECTIVENESS OF SONG-BASED INSTRUCTION IN EARLY YEARS AE CLASSROOMS: EXTENDING MILLINGTON’S FRAMEWORK. - Dildora Radjabova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Song-based instruction is a staple of early years language education, yet its implementation often lacks a rigorous pedagogical framework. This article evaluates the effectiveness of songs in Accelerated English (AE) classrooms by extending Millington’s (2011) tripartite framework—preparation, core activity, and follow-up. While Millington focused primarily on vocabulary acquisition, this extension incorporates elements of pronunciation, listening comprehension, and affective filter reduction. Through a review of current literature and a proposed methodological approach, the study finds that structured song-based tasks significantly improve student engagement and retention compared to passive listening.